IMPLEMENTATION OF STATE CONFISCATED OBJECTS STORAGE HOUSES (RUPBASAN) BY LAW NUMBER 8 OF 1981 CONCERNING LAW BOARD LAW OF CRIMINAL EVENTS (KUHAP) - Eleanora, Fransiska Novita (Tadulako Law Review, 2019)
State confiscated storage house (rupbasan) in the provisions of the Criminal Procedure Code (Criminal Procedure Code) is a place of storage of confiscated objects or the proceeds of state booty in the form of movable and immovable goods to be stored after receiving a permanent decision from the court must incorporated into rupbasan, in carrying out its duties, Rupbasan still experiencing obstacles both internally or externally to be addressed properly, so that Rupbasan as a place to keep confiscated objects remain existence and competence according to its function. Internal obstacles are lack of human resources (HR), limited facilities / infrastructure, lack of regulation about Rupbasan, unknown level of examination case of goods deposited, no time limit of goods custody, External obstacles of assumption law enforcement officers that rupbasan has not been able to manage / storing confiscated objects of state, and there is no similar perception of society related to rupbasan, especially related institutions.